The role of place branding in promoting social capital in urban areas (case study: Ahvaz, Iran) - Ramezi, Mansour; Yeganeh, Mansour; Bemanian, Mohammadreza (Frontiers in Built Environment, 2022)
Social capital is one of the requirements of quality and good urban living. Social capital will lead to trust and security of participation and social solidarity of spatial belonging and shared values. In urban neighborhoods, various factors can lead to the production and promotion of social capital. The explanatory claim is that branding a place through architectural elements can lead to the production and reproduction of social capital in neighborhoods. The research method of this article is a survey using a closed questionnaire. The conceptual model of this research has been tested in thirteen neighborhoods of Ahvaz city and using the opinions of 663 residents of these neighborhoods. The research results show that social capital in neighborhoods is directly related to the brand of those neighborhoods. Having a readable neighborhood center, distinct architectural style, familiar and natural symbols and signs, significant green and blue infrastructure including rivers, significant communication bridges, antiquity and originality of the neighborhood, a hierarchical system in pedestrian and pedestrian access and legibility of space are the most important components in Becoming a brand. Identity branding and physical differentiation have the most significant impact on increasing social capital. The functional aspect of place branding also can promote social capital in neighborhoods. This issue is most effective when neighborhoods do not have many identities and physical differentiation.